Reprint of: Impact of endometriosis on quality of life and work productivity: A multicenter study across ten countries - Nnoaham, KE; Hummelshoj, L; Webster, P; d'Hooghe, T; de Cicco Nardone, F; de Cicco Nardone, C; Jenkinson, C; Kennedy, SH; Zondervan, KT (Elsevier, 2019)
Object: To assess the impact of endometriosis on health-related quality of life (HRQoL) and work productivity.